Algae as production systems of bioactive compounds. Issue 2 (28th January 2015) - Michalak, Izabela; Chojnacka, Katarzyna
Abstract : Algal extracts are gaining increasing interest due to their unique composition and possibilities of wide industrial applications. Various extraction techniques are used for conversion of algal biomass into extracts. Recently, attention of scientists has been paid to novel methods, such as enzyme‐assisted extraction, microwave‐assisted extraction, pressurized liquid extraction, supercritical fluid extraction, and ultrasound‐assisted extraction, which enable the extraction of biologically active compounds without their degradation. In this review, the properties of biologically active compounds extracted from the biomass of algae reported in the literature are presented in a structured way. Algal extracts contain compounds such as carbohydrates, proteins, minerals, oil, fats, polyunsaturated fatty acids as well as bioactive compounds such as antioxidants (polyphenols, tocopherols [vitamin E], vitamin C, mycosporine‐like amino acids), and pigments, such as carotenoids (carotene xanthophyll), chlorophylls, and phycobilins (phycocyanin, phycoerythrin), which possess antibacterial, antiviral, antifungal, antioxidative, anti‐inflammatory, and antitumor properties. Finally, we assemble a list of applications of algal extracts in different developing branches of agriculture (biostimulants, bioregulators, feed additives) and in pharmaceutical industry.